Case Report: Clinical Features of Congenital Portosystemic Shunts in the Neonatal Period - Xu, Suhua; Zhang, Peng; Hu, Liyuan; Zhou, Wenhao; Cheng, Guoqiang (Frontiers in Pediatrics, 2021)
Objective: The aim of this single center retrospective study was to analyze the clinical characteristics, treatment options, and course of neonatal-onset congenital portosystemic shunts (CPSS). Methods: We included all patients with CPSS who presented with clinical symptoms within the neonatal period in our institution between 2015 and 2020. Results: Sixteen patients were identified, including thirteen patients with intrahepatic portosystemic shunts (IPSS) and three patients with extrahepatic portosystemic shunts (EPSS). Median age of diagnosis was 16 days (range prenatal 24 weeks – 12 months). Hyperammonemia (60%), neonatal cholestasis (44%), elevated liver enzyme (40%), hypoglycemia (40%), thrombocytopenia (38%) and coagulation abnormalities (23%) appeared in neonatal CPSS. Twelve patients (75%) presented with congenital anomalies, of which congenital heart disease (CHD) (44%) was the most common. Thirteen patients with IPSS initially underwent conservative treatment, but two of them were recommended for the catheter interventional therapy and liver transplantation, respectively, due to progressive deterioration of liver function. Spontaneous closure occurred in nine patients with IPSS. The shunt was closed using transcatheter embolization in one patient with EPSS type II. Another patient with EPSS type II underwent surgical treatment of CHD firstly. The remaining patient with EPSS type Ib received medical therapy and refused liver transplantation. Conclusion: Hyperammonemia, neonatal cholestasis, elevated liver enzyme, hypoglycemia and thrombocytopenia are the main complications of neonatal CPSS. And CPSS is associated with multiple congenital abnormalities, especially CHD. IPSS may close spontaneously, and conservative treatment can be taken first. EPSS should be closure to prevent complications.